Spectrum of Neurological Disorders: Experience in Specialized Outpatient Clinic in Bangladesh (Journal of Medicine, 2012)
Objective: To examine the burden of neurologic disorder as encountered in a specialized neurology clinic at tertiary care level. Methods: This retrospective study was carried out in specialized neurology outpatient clinic of Dhaka Medical College Hospital from July 2010 to June 2011, which included 3173 patients. Data were collected through a predesigned questionnaire from the hospital database kept at the clinic. Result: Among all the patients attending outpatient clinic, 88.7% had 44 types of neurological disorders. Distribution of disease was similar in all age group from 21-30 years to 51-60 years. Stroke (28.2%) and Headache (24.7%) were two most common neurologic disease, where headache was prevalent among female aged less than 30 years and stroke in male of >40 years. Epilepsy, peripheral neuropathy, Parkinson’s disease, pseudo vertigo were also present in a considerable number of patients. Patients with peptic ulcer (3.02%), anxiety neurosis (2.6%) and other non neurological disease were also given consultation in the clinic. Conclusion: Neurological diseases are not uncommon. Different diseases predominate in different age and sexes. Knowing pattern of disease distribution in community will help managing them properly. DOI: http://dx.doi.org/10.3329/jom.v13i1.10045 JOM 2012; 13(1): 39-42